Ethnomathematics-Based Live Worksheets on Flat Shapes Using Endek Tretes, Tumpal, and Jumputan Motifs for Fourth Grade Students - Agustina, Kadek Intan; Gusti Ngurah Sastra Agustika; Chindytia (Journal for Lesson and Learning Studies, 2025)
Limitations in mathematics learning media have an impact on low student understanding and learning outcomes, particularly in the subject of flat shapes in fourth grade elementary school. This study aims to develop valid and effective digital worksheets based on ethnomathematics using endek tretes, tumpal, and jumputan woven fabrics to improve student learning outcomes. The development model used is ADDIE, encompassing the stages of analysis, design, development, implementation, and evaluation. The research subjects were 28 fourth-grade elementary school students. Data were collected through interviews, observations, questionnaires, and tests, and analyzed using qualitative and quantitative descriptive analysis, as well as paired-sample t-tests. The validation results indicate that this media is highly suitable for use, with scores of 90.90% from content experts, 91.67% from design experts, and 92.19% from media experts. Individual and small group tests yielded scores of 96.20% and 97.21%, respectively. The effectiveness test showed a significant improvement in student learning outcomes with a tvalue of 22.439 > ttable 1.703. Thus, this ethnomathematics-based digital LKPD has been proven to be valid, feasible, and effective for use in learning about flat shapes, and contributes to enriching the variety of meaningful learning media in elementary schools.